New magnetic nanocomposite materials - Corr, Serena (Trinity College (Dublin, Ireland). School of Chemistry, 2007)
The main aim of this project is to develop new iron oxide based nanomaterials with potential biomedical applications. This work involves the synthesis of various magnetite, maghemite and cobalt ferrite nanocomposites, the study of these materials using different instrumental techniques and the evaluation of their potential biomedical applications.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin